2020
DOI: 10.1021/acscatal.0c01099
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Location of Single Copper Atoms in Polymeric Carbon Nitride for Enhanced Photoredox Catalysis

Abstract: Introducing single-atom metals (SAMs) is a promising strategy to improve photocatalysis of polymeric carbon nitride (PCN), but current studies are limited to loading SAMs on the surface of PCN to serve as active sites. Herein, we report an intercalation-structured hollow carbon nitride sphere composed of carbon nitride nanosheets (HCNS) with atomically dispersed Cu1N3 moieties embedded within nanosheets (Cu1@HCNS) prepared by a facile molecular assembly approach. It exhibits far superior photoredox catalysis t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(61 citation statements)
references
References 60 publications
2
55
0
Order By: Relevance
“…15,16 Then, designing a specific catalyst that could abstract hydrogen from the hydrogen donor efficiently and drive the reaction under neutral environment was essential. As a metal-free, environmentally friendly visible light absorbable photocatalyst, polymeric carbon nitride (PCN) has raised wide concern in photodegradation of pollutants, [17][18][19] reduction of CO 2 , 20,21 H 2 production [22][23][24] and, in particular, organic photosynthesis. [25][26][27][28][29][30][31][32][33] Many works had been reported that the surface modified methods can regulate the catalytic performance of the polymeric carbon nitride, and even control the selectivity of the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Then, designing a specific catalyst that could abstract hydrogen from the hydrogen donor efficiently and drive the reaction under neutral environment was essential. As a metal-free, environmentally friendly visible light absorbable photocatalyst, polymeric carbon nitride (PCN) has raised wide concern in photodegradation of pollutants, [17][18][19] reduction of CO 2 , 20,21 H 2 production [22][23][24] and, in particular, organic photosynthesis. [25][26][27][28][29][30][31][32][33] Many works had been reported that the surface modified methods can regulate the catalytic performance of the polymeric carbon nitride, and even control the selectivity of the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…melamine-Ag complex (Mel-Ag) with cyanuric acid followed by a pyrolysis process in N 2 (Figure 1a). According to our previous reports, 39,42 1h,i, highlighted by yellow circles). Supporting Information Figure S4 and Supporting Information Table S1 implies no obvious influence on the textural properties and N/C ratio after the introduction of a low amount of Ag or Cu atoms within the framework.…”
mentioning
confidence: 70%
“…39,[42][43][44] A new peak deconvoluted on N 1s XPS spectra of Ag 1 N -HCNS and Cu N 3 -HCNS (Figures 2ac) can be assigned to Ag−N bonding and Cu−N bonding, respectively. 39,40 The lowering content of pyridinic N (Supporting Information Table S2) is a further indicator of coordination of Ag or Cu with pyridinic N. 39 Furthermore, the remarkably increased intensity of Ag 3d and Cu 2p XPS peaks after Ar plasma etching (Supporting Information Figure S6) indicates the implantation of Ag and Cu atoms within the carbon nitride nanosheets of Ag 1 N 3 -HCNS and Cu 1 N 3 -HCNS, respectively. 39 The electronic structure and local coordination environment of Ag and Cu species are further investigated by X-ray absorption spectroscopy (XAS).…”
mentioning
confidence: 99%
“…Zhao and co‐workers reported hollow carbon nitride spheres with an intercalation structure, which is composed of atom‐dispersed carbon nitride nanosheets. [ 94 ] These nanosheets were prepared by a simple molecular assembly method and each Cu atom coordinates with three N atoms, giving a configuration of Cu 1 –N 3 . The resultant material performed much better in photocatalytic H 2 production than unmodified carbon nitride nanosheets (HCNS) and HCNS modified by Cu 1 –N 3 groups on the surface of the nanosheets.…”
Section: Coordination Geometry Electronic Structure and Characterization Of Carbon Nitride–supported Smasmentioning
confidence: 99%